R&D activities and extensive margins of exports in manufacturing enterprises: First evidence for Germany - Joachim Wagner (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2015)
This paper uses a new tailor-made data set to investigate for the first time the links between innovation activities (measured by employees active in research and development) and the extensive margins of exports (number of destination countries; number of goods exported) for manufacturing enterprises in Germany, the third largest exporter of goods on the world market. It documents that more innovative firms outperform less innovative firms at both margins of exports - they export more goods and they export to a larger number of countries. All these differences are statistically highly significant and large from an economic point of view.
Keywords: F14; 330; extensive margins of exports; Germany; innovation; research and development